2006
DOI: 10.1128/iai.00949-06
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1-Deficient Mice Show Defects in Innate Immunity and Inflammatory Immune Response during Salmonella enterica Serovar Typhimurium Infection

Abstract: A number of studies have shown an association of pathogens with caveolae. To this date, however, there are no studies showing a role for caveolin-1 in modulating immune responses against pathogens. Interestingly, expression of caveolin-1 has been shown to occur in a regulated manner in immune cells in response to lipopolysaccharide (LPS). Here, we sought to determine the role of caveolin-1 (Cav-1) expression in Salmonella pathogenesis. Cav-1 ؊/؊ mice displayed a significant decrease in survival when challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
80
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 45 publications
10
80
4
Order By: Relevance
“…The cav-1 2/2 mice displayed increased susceptibility to bacterial infection, whereas macrophages derived from these mice exhibited enhanced inflammatory responses to bacterial endotoxin (43). Previously, we have demonstrated an anti-inflammatory function of cav-1 expression in vitro with respect to the inhibition of pro-inflammatory cytokines production during endotoxin-induced inflammation in macrophages (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cav-1 2/2 mice displayed increased susceptibility to bacterial infection, whereas macrophages derived from these mice exhibited enhanced inflammatory responses to bacterial endotoxin (43). Previously, we have demonstrated an anti-inflammatory function of cav-1 expression in vitro with respect to the inhibition of pro-inflammatory cytokines production during endotoxin-induced inflammation in macrophages (46).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cav-1 has also been implicated as a modulator of innate immunity and inflammation (43)(44)(45). The cav-1 2/2 mice displayed increased susceptibility to bacterial infection, whereas macrophages derived from these mice exhibited enhanced inflammatory responses to bacterial endotoxin (43).…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1 is a key immunomodulatory molecule in the inflammatory response (13,16,67,71), and decreased expression of caveolin-1 in murine alveolar and peritoneal macrophages has a proinflammatory outcome (67). Fibrinous polyserositis is inflammation of the serous tissues with fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathogenesis of H. parasuis infection remains largely unknown. A recent study demonstrated that caveolin-1 knockout mice were markedly susceptible to Salmonella enterica serovar Typhimurium (13). Whether caveolin-1 is also involved in the pathogenesis of Glasser's disease in pigs is of great interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation